Breeding for Low Temperature Stress Tolerance in Reproductive Stage of Rice (Oryza sativa L.) - Loitongbam, Bapsila; Chandra, Kailash; Bisen, Prashant; Thakur, Namrata, Padma; Sandhya (International Journal of Bio-resource and Stress Management, 2017)
Rice is a cold-sensitive plant that has its origin in tropical or subtropical areas and cold damage can cause serious yield losses. Low temperature affects the rice cultivation mainly in two stages of development i.e. seedling and booting. In both of them, cold temperature has harmful effects on crop productivity. Low temperature during the reproductive stage in rice causes degeneration of spikelets, incomplete panicle exsertion and increases spikelet sterility thus reducing grain yield. The most sensitive stage to low temperature is the booting stage. The percentage of fertile spikelet has been used as effective parameters of cold tolerance of rice at booting stage. Low temperature at booting stage causes anther injury, degeneration of young microspores, resulting in high spikelet sterility and reduced rice yield. Understanding molecular mechanism of cold stress in rice became an important step since it will increase the precision in screening in addition to phenotypic evaluation. Cold tolerance in rice is a quantitative trait controlled by multiple genes. Because it is often difficult to directly associate plant phenotypes with the genes responsible for cold tolerance, therefore marker-assisted selection is an effective means of developing cold-tolerant cultivars. Dissecting cold stress-mediated physiological changes and understanding their genetic causes will facilitate the breeding of rice for cold tolerance. Research on quantitative trait loci (QTL) related to cold stress at the germination, seedling and reproductive stages that will provide useful information to accelerate progress in breeding programme.